Dense Platinum/Nickel Oxide Heterointerfaces with Abundant Oxygen Vacancies Enable Ampere‐Level Current Density Ultrastable Hydrogen Evolution in Alkaline. (9th December 2022) - Wang, Kaixi; Wang, Shuo; Hui, Kwan San; Li, Junfeng; Zha, Chenyang; Dinh, Duc Anh; Shao, Zongping; Yan, Bo; Tang, Zikang; Hui, Kwun Nam
Abstract: Platinum (Pt) remains the benchmark electrocatalyst for alkaline hydrogen evolution reaction (HER), but its industry‐scale hydrogen production is severely hampered by the lack of well‐designed durable Pt‐based materials that can operate at ampere‐level current densities. Herein, based on the original oxide layer and parallel convex structure on the surface of nickel foam (NF), a 3D quasi‐parallel architecture consisting of dense Pt nanoparticles (NPs) immobilized oxygen vacancy‐rich NiOx heterojunctions (Pt/NiOx ‐OV ) as an alkaline HER catalyst is developed. A combined experimental and theoretical studies manifest that anchoring Pt NPs on NiOx ‐OV leads to electron‐rich Pt species with altered density of states (DOS) distribution, which can efficiently optimize the d‐band center and the adsorption of reaction intermediates as well as enhance the water dissociation ability. The as‐prepared catalyst exhibits extraordinary HER performance with a low overpotential of 19.4 mV at 10 mA cm −2, a mass activity 16.3‐fold higher than that of 20% Pt/C, and a long durability of more than 100 h at 1000 mA cm −2 . Furthermore, the assembled alkaline electrolyzer combined with NiFe‐layered double hydroxide requires extremely low voltage of 1.776 V to attain 1000 mA cm −2, and can operate stably for more than 400 h, which is rarely achieved. Abstract : A 3D quasi‐parallel architecture consisting of dense Pt nanoparticles immobilized oxygen‐vacancy‐rich NiOx heterojunctions (Pt/NiOx ‐OV ) is successfully constructed on nickel foam. The self‐supporting electrode exhibits extraordinary alkaline hydrogen evolution reaction performance with low overpotential and high mass activity. Besides, the assembled alkaline electrolyzer combined with NiFe‐layered double hydroxide can operate stably for more than 400 h at 1000 mA cm −2 .